Profile of Senior Business Failure - del Olmo-Garcia, Francisco; Crecente-Romero, Fernando Javier; del Val-Nunez, Maria Teresa; Dominguez-Fabian, Inmaculada (Transformations In Business & Economics, 2024)
Demographic change and labour market challenges for senior professionals have made senior entrepreneurship one of the pillars for the older generation. Despite the fact that entrepreneurial activity is the engine of growth and development of modern economies, not enough attention is paid to business failure and the need to generate a sustainable entrepreneurial fabric over time. In this sense, the academic literature has not yet addressed in sufficient depth the factors that characterise senior entrepreneurs who fail.The aim of this paper is to identify the main socio-demographic features that characterise senior entrepreneurs who fail in their business activity, differentiating between the expansionary and contractionary stages of the economic cycle, which has been revealed as an important factor to be taken into account in the literature on business failure. The case of Spain, one of the countries in the world with the highest life expectancy and the greatest importance of senior professional connectivity, has been taken as a case study.For this purpose, based on micro-data from the Spanish Labour Force Survey and for the period from March 2005 to December 2022, logistic regression models have been developed to identify key socio-demographic factors in the probability of failure: the sector and region of activity, the existence of a spouse and whether or not he/she has his/her own professional career, educational level, sex, nationality, and the existence of dependent children in the family home.The results allow us to understand the factors that are related to senior entrepreneurial failure in order to define public policies (education, sectoral or regional cohesion policies, for example) that help entrepreneurs generate sustainable projects over time, beyond the stage of the economic cycle.
Keywords: elderly entrepreneurship; business failure; economic cycle; labor force survey; sociodemographic profile